Trade-Off between Sampling Frequency and Duration and Their Influences on the Estimation of Space Use of Japanese Macaques - Kana Terayama; Hiroshi Ebihara; Hironori Seino; Masaaki Takiguchi; Motomi Genkai-Kato (International Journal of Zoology, 2023)
Space use, estimated based on location data, provides fundamental knowledge in the basic and applied ecology of wild animals. There is a trade-off between sampling frequency and duration in location data which are collected from a tracking device attached to an animal because the battery of the device has a limited life. In this study, we assessed how different combinations of sampling frequency and duration would affect estimates for home-range size and maximum utilization area (MUA) of Japanese macaques, using datasets subsampled by reducing frequency and/or duration from the original dataset. Estimates of MUA were likely to be overestimated if the sampling duration was shorter than 80 days for Japanese macaques. Reductions in sampling frequency and duration had opposite effects on estimates of home-range size: the estimated area decreased with decreasing sampling duration, while it increased with decreasing sampling frequency. Moreover, these opposite effects can be offset when the sampling frequency and duration are simultaneously reduced. We discussed the applicability of our results to animals other than Japanese macaques and how to design the sampling frequency and duration in future research.